THE STUDENTS’ PERCEPTIONS ON THE USE OF YOUTUBE IN LEARNING VOCABULARY - Madani, Noviani Sri; Hidayat, Muhamad Taufik; Hasim, Wahid (IPI Garut Press, 2023)
This study aims to determine the students' perceptions of YouTube as a medium for learning English vocabulary. This research approach is qualitative research using a case study methodology. Semi- structured interviews and observation of non- participants were used as instruments for data collection. This research was conducted at a secondary school located in Garut, West Java. The participants in this study were ten eighth-grade students who were graded high, medium, and low in English. The results showed that most students felt comfortable using YouTube to learn vocabulary because it was easy to understand and had more exciting visualization. In addition, they feel motivated to learn vocabulary using YouTube because learning is more fun than other learning media. Furthermore, all participants experienced nasty things when using YouTube; internet access was unstable, and lots of advertisements while watching learning videos caused them to lose concentration. However, all participants positively perceived using YouTube as a medium for learning English vocabulary. That way, educators should be able to expand their skills in implementing YouTube as a medium for learning vocabulary with new strategies, and it is also hoped that educators can take a more proactive approach to help students learn English vocabulary.